1978
DOI: 10.1159/000136790
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant Activity and Selective Inhibition of NAD-Dependent Oxidations by 1,2,4-Trisubstituted-5-Imidazolones

Abstract: Nine 1-(3,4-dimethoxyphenylethyl)-2-methyl-4-(substituted benzylidene)-5-imidazolones were synthesized, characterized by their sharp melting points, elemental analyses and infrared spectra and evaluated for anticonvulsant activity. All l,2,4-trisubstituted-5-imidazolones at a dose of 100 mg/kg i.p. possessed anticonvulsant activity and the degree of protection observed against pentylenetetrazol-induced convulsions in mice ranged from 20 to 60%. These 1,2,4-trisubstituted-5-imidazolones selectively inhibited in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The corresponding methyl ether m - MBDI was also prepared. It is noteworthy that, despite the previously unknown nature of m - HBDI itself, several 2-methyl-substituted derivatives exhibiting various biological activities have been synthesized 2 Left column: absorption spectra of p - HBDI (top) and m - HBDI (bottom) in methanol/water (MW) 1/1 vol.…”
mentioning
confidence: 99%
“…The corresponding methyl ether m - MBDI was also prepared. It is noteworthy that, despite the previously unknown nature of m - HBDI itself, several 2-methyl-substituted derivatives exhibiting various biological activities have been synthesized 2 Left column: absorption spectra of p - HBDI (top) and m - HBDI (bottom) in methanol/water (MW) 1/1 vol.…”
mentioning
confidence: 99%
“…and reported their anticonvulsant activity. These results showed that introduction of a substituent in the phenyl nucleus of benzylidene moiety increased the anticonvulsant activity [61].…”
Section: Joshimentioning
confidence: 88%